Crisis in a divided Korea a chronology and reference guide - Matray, James I. 1948- (Santa Barbara, California ABC-CLIO, 2016)
"This book provides scholars and students examining Korea's place in modern world politics with an invaluable resource for understanding the causes, course, and consequences of the ongoing crisis on the Korean Peninsula. Provides readers with an understanding of the reasons for the existence of two nations on the Korean Peninsula. Exposes how outside powers have intervened in Korean affairs throughout its modern history--with disastrous results. Explains the development of North Korea into an isolated nation with a government determined to possess nuclear weapons. Suggests avenues for Korea's reunification and the achievement of permanent peace and stability on the peninsula"-- Provided by publisher.
Hermit kingdom -- Imperialist prize -- A house divided -- Koreans invading Koreans -- Fighting for peace -- Guerilla dynasty -- Dictated development -- Cold War remnant -- Uncertain allies -- Needless quarrel -- Chronology -- Biographies -- Primary documents.
Includes bibliographical references (pages 363-367) and index.
Keywords: Korean reunification question (1945-); Korea -- History; Korea (South) -- History; Korea (South) -- Foreign relations; Korea (North) -- History; Korea (North) -- Foreign relations